Netralisasi air limbah penambangan emas di Blok Jalur 7 Bolaang Mongondow dengan menggunakan larutan kapur - Malureng, Niciawati Dg; Suryanto, Andi; Yani, Setyawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Bolaang Mongondow region, especially in Tanoyan Selatan Village within the Lolayan District, presents considerable promise for the extraction of economically significant minerals, including gold ore. In this region, the practice of small-scale gold mining frequently utilizes cyanidation methods, which present significant environmental hazards. This research endeavors to investigate the effectiveness of Lobong lime and Kemindo lime in neutralizing the pH of mining wastewater, with particular emphasis on the impact of lime type and concentration on pH levels. The methodology for treating wastewater entailed the incorporation of lime powder into mining wastewater at diverse concentrations of 0.03 g, 0.04 g, 0.05 g, 0.08 g, 0.10 g, and 0.12 g, accompanied by stirring intervals of 1 minute, 3 minutes, 5 minutes, 7 minutes, and 10 minutes. The results indicated that Kemindo lime consistently surpassed Lobong lime in elevating pH levels. Moreover, the level of lime demonstrated a direct positive relationship with the enhancement of pH; increased lime concentrations led to markedly higher pH values. The findings highlight the essential importance of choosing the correct type and concentration of lime in wastewater treatment to improve both water and soil quality, consequently reducing environmental repercussions.